El maternés de madres peruanas: Una descripción psicolingüística sobre los estilos de habla - Lovón Cueva, Marco Antonio (2020)
Mothers often speak to their children from an early age to stimulate their communication skills and the learning of their mother tongue. This special form of communication developed between mothers (and caregivers in general) and children is called baby talk. In the acquisition process, baby talk play a central role as providers of linguistic input. The objective of this study is to analyze the Peruvian baby talk. Methodologically, two mothers and their children in early childhood have been selected and their verbal interactions recorded. In this study, the linguistic characteristics and the styles of this baby talk are described. Likewise, the difference in speech between the receptive-style mother and the unreceptive-style mother is presented.